Study on incidence of anoestrus and blood biochemical constituents in non cyclic and cyclic crossbred cows - YADAV, Y P; SINGH, A P; KUNJ, VIVEK; AKHTAR, M H; ROY, G P; SINGH, C (The Indian Journal of Animal Reproduction, 2023)
Incidence of anoestrus in crossbred cows (263) having reproductive disorder was studied during different seasons broughtto the outdoor clinic of Gynaecology department of Bihar Veterinary College, Patna. The data showed the non-significant effect ofseason and month on anoestrus condition in cows. Overall percentage of anoestrus cows was found to be 30.42%. The highestincidence (47.62%) was recorded in March and lowest (14.28%) in May. During the study IO normal cycling and 30 anoestrus cowswere selected randomly for study of biochemical profile blood glucose and serum alkaline phosphatase from the blood samplecollected on 0,15th and 30th day . The observation revealed that significant difference (P
Keywords: Crossbred cows; cycling; anoestrus; blood biochemical constituents